2020
DOI: 10.1161/strokeaha.119.028246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Patients With Ischemic Stroke With Prestroke Disability

Abstract: Background and Purpose— We aimed to compare functional and procedural outcomes of patients with acute ischemic stroke with none-to-minimal (modified Rankin Scale [mRS] score, 0–1) and moderate (mRS score, 2–3) prestroke disability treated with mechanical thrombectomy. Methods— Consecutive adult patients undergoing mechanical thrombectomy for an anterior circulation stroke were prospectively identified at 2 comprehensive stroke centers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 27 publications
8
62
1
1
Order By: Relevance
“…The application of mechanical thrombectomy in the treatment of acute ischemic stroke has been studied for many years. The incidence of satisfactory outcomes in this study was approximately 70%, which is similar to previous studies of acute ischemic stroke caused by occlusion of other arteries (16,17). Furthermore, in agreement with previous studies (18,19), the mortality rate in this study was 17% within 90 days after the procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The application of mechanical thrombectomy in the treatment of acute ischemic stroke has been studied for many years. The incidence of satisfactory outcomes in this study was approximately 70%, which is similar to previous studies of acute ischemic stroke caused by occlusion of other arteries (16,17). Furthermore, in agreement with previous studies (18,19), the mortality rate in this study was 17% within 90 days after the procedure.…”
Section: Discussionsupporting
confidence: 92%
“…These results emphasize that pre-stroke dependent patients have a higher risk of suffering death after ET, likely reflecting higher rates of comorbidities in this patient population. Although not the focus of our study, but in support of this notion, the prestroke dependent patients had significantly more comorbidities than independent patients in the aforementioned MR Clean Registry and analysis of the two comprehensive stroke centers (8,9). Aside from a higher disease burden caused by preexisting comorbidities, the dependent patients are more likely to have other complications than SICH.…”
Section: Discussionsupporting
confidence: 55%
“…Since pre-stroke disability will continue to rise in the coming years (7), the potential impact of ET on outcome in patients with prior disabilities has received increased attention. In fact, several recent case series as well as an analysis of the MR Clean Registry have revealed favorable functional and procedural outcome rates after ET in patients with prior disabilities compared to those without pre-stroke disability (8)(9)(10)(11)), yet all of these studies lacked a control group, such that the true treatment effect of ET in pre-stroke disabled patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients who underwent thrombectomy in the NIS were older, had a higher proportion aged 80 years or older, and had more comorbidities than those who underwent thrombectomy in HERMES. Previous studies have shown higher mortality and less favorable outcomes after thrombectomy in patients aged 80 years or older (24,25) and in patients with worse premorbid disability (32). However, fewer ICA strokes in the NIS thrombectomy cohort would have favored better outcomes in this group.…”
Section: Rates Reasons and Risks For Readmissionmentioning
confidence: 96%